Les mobilités éprouvantes. Regards sur les pénibilités des déplacements ordinaires - Christophe Enaux; Pierre Lannoy; Sébastien Lord (Articulo: Journal of Urban Research, 2011)
Beside the intellectual excitement that surrounds the emergence of the study of daily mobilities as a vibrant new field of research for the social sciences, it seems that some dimensions of the phenomenon still unexplored. Indeed how arduous daily travels are is hardly known. And yet, in a context of growing mobility experiences and demands, it seems very likely that these experiences are becoming more demanding. From a general perspective, it can be argued that three types of constraints affect the daily mobility practices. First, as a large amount of people are working outside their home, their daily journeys are generated and framed by their professional occupation, its location and type. Second, rhythms of school life very deeply shape the need for and modes of daily travels, and therefore the uses of public circulatory spaces. Third, journeys to places of consumption, in the broader sense of the term (shops, public services, leisure or cultural activities, tourism places, etc.), are constrained by their locations and opening times. All those constraints put daily mobilities under pressure: time constraints, contradictory individual demands for journeys and/of transport modes, and complex management of available resources are at stake every day. In this perspective, the difficult nature of daily mobilities can be investigated through the main spheres depicted here: the domestic, occupational, and public spheres. They can be considered as the structuring poles that generate and govern the often contradictory, and always complex, needs for daily travels. This special issue will present some selected contributions resulting from the last international conference organized at the Université Libre de Bruxelles in March 2010 by the working group “Spatial Mobilities and Social Fluidity” of the Association internationale des sociologues de langue française (AISLF). They will focus, from different disciplinary perspectives, on the arduous dimensions of daily mobilities, i.e. on these diverse circumstances in which ordinary people are induced to be mobile and to experience mobility as a complex task. Some aspects to be investigated will be: mobilities of teenagers; the tiring experiences of public transport networks; and the constraining features of sociospatial locations, of institutions (public services, road controls, and prisons) or of particular political contexts.